2016
DOI: 10.1108/ijhrh-05-2015-0015
|View full text |Cite
|
Sign up to set email alerts
|

Belief systems enforcing female genital mutilation in Europe

Abstract: Purpose – Despite numerous studies on FGM, little is known about belief systems that support FGM in the EU. The purpose of this paper is to explore the dynamic nature of belief systems and enforcement mechanisms that perpetuate FGM among three African migrant communities in the EU. Design/methodology/approach – This paper is based on data collected through community-based participatory action research in three communities: Eritrean and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Despite such abandonment and low support for FGC, studies have also documented a sense of continuity in the underlying cultural values among Somalis in the diaspora [45,46]. A study including Somalis in Norway found a prevailing strong association between infibulation and its underlying cultural values relating to virginity and virtue [21].…”
Section: Introductionmentioning
confidence: 99%
“…Despite such abandonment and low support for FGC, studies have also documented a sense of continuity in the underlying cultural values among Somalis in the diaspora [45,46]. A study including Somalis in Norway found a prevailing strong association between infibulation and its underlying cultural values relating to virginity and virtue [21].…”
Section: Introductionmentioning
confidence: 99%
“…The qualitative data collected was examined using thematic analysis. Results of the CPAR have been published elsewhere [11,25].…”
Section: Element 2: Understanding the Social Norm Perpetuating Fgmmentioning
confidence: 99%
“…Research undertaken with Somali communities living in Sweden suggests that FGM becomes counter-normative following migration [9,10]. However the evidence is much less clear in other EU countries and amongst other FGM affected communities/ethnic groups [11,12]. Research undertaken by Alhassan et al [11] as part of the REPLACE Project, suggests that for some migrant groups living in Italy, Spain and Portugal, the move to the EU has strengthened their beliefs that perpetuate FGM.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations